Analysis of School Climate in the Unesa School Lab - MV. Roesminingsih; Widya Nusantara; IGL Putra Eka Prismana; Monica Widyaswari (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
This study aims to analyze the school climate in the Unesa Lab School environment. This study uses a descriptive quantitative approach. This research took place in nine schools, including two kindergartens, two elementary schools, three junior high schools, one high school, and one vocational school. The study results show that the overall school climate in the Unesa Lab environment is excellent, evidenced by the average gain of 4.19. However, suppose one looks at them one by one. In that case, two schools are in the excellent category: Unesa Lab School Kindergarten 1 and Unesa Lab School Elementary School 1. Of all the indicators that tend to get low scores compared to the others are (1) the happy atmosphere of the students is not maximized, and there are still doubts in doing the assignment; (2) there is secrecy in providing information, so mutual suspicion still appears; (3) the synergy between school principals and teachers, between teachers, and teachers and students in the teaching and learning process is not maximized; (4) the teaching and learning facilities provided are not by their purpose; and (5) the assistance given has not been maximized for any difficulties that arise as a result of assignments imposed on students.